2014
DOI: 10.1021/jp5054666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mo-Incorporation in the TiO2 Lattice: A Mechanistic Basis for Photocatalytic Dye Degradation

Abstract: Photocatalytic activity of TiO 2 (anatase) is appreciably enhanced by substitutional doping of Mo in anatase lattice, in conjunction with the incorporation of nanostructured MoO 3 within the parent anatase lattice. The photocatalyst material was characterized in detail using X-ray diffraction, Raman spectroscopy, diffuse reflectance (DR-UV− Vis spectroscopy), X-ray photoelectron spectroscopy, and electron microscopy. Photocatalysis experiments were conducted using a model rhodamine-B (Rh−B) dye reaction using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 75 publications
4
48
0
Order By: Relevance
“…The new peaks in the spectrum are associated with the intermediate products formed during degradation. The NMR results further confirmed that the de-ethylation and degradative changes of RhB occurs during the photo degradation processes 32,33 .…”
Section: Resultssupporting
confidence: 64%
“…The new peaks in the spectrum are associated with the intermediate products formed during degradation. The NMR results further confirmed that the de-ethylation and degradative changes of RhB occurs during the photo degradation processes 32,33 .…”
Section: Resultssupporting
confidence: 64%
“…Moreover, the peak at 230.88 eV suggests that the presence of the Mo 5+ , which is consistent with the reported Mo 5+ and Mo 6+ states inherently in the MoO 3 itself. 34 After the calculation by XPS, the atomic ration of Mo/Ti is 17.4% (more than 10 %), indicating that the phase segregation of ultrafine MoO 3 crystals on the surface of TiO 2 , which is demonstrated by the XRD result and TEM observation.…”
Section: Morphology and Compositionmentioning
confidence: 91%
“…A c c e p t e d M a n u s c r i p t Edited June 15 6 27, [33][34][35][36][37][38][39][40][41] and non-metals (e.g., C, B, F, N, S, etc.) [28,30,[42][43][44][45][46][47], co-doping of metals/nonmetals with other metals/non-metals [48][49][50][51][52], coupling with carbonaceous nanoscale materials (fullerene (C 60 ), carbon nanotubes (CNTs) and graphene) [53][54][55][56][57][58][59] and metal oxides (WO 3 [60], [61], SnO 2 [62], MoO 3 [63], SiO 2 [64]), as well as capping (coating of one semiconductor or metal nanomaterial on the surface of another semiconductor or metal nanomaterial core) of TiO 2 [65,66].…”
Section: Page 6 Of 70mentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t Edited June 15 38 As briefly mentioned before, metal/non-metallic doping enhances the photocatalytic activity by either reducing the effective bandgap (introducing intraband states) or increasing the efficient separation of generated electrons-hole pairs. In general, metal doping is achieved by replacing Ti 4+ with other metallic ions, while O 2-anions is replaced with low atomic weight non-metals in non-metallic doping [6,175,176].…”
Section: Page 38 Of 70mentioning
confidence: 99%